GAMBARAN PELAKSANAAN STANDAR PELAYANAN KEFARMASIAN DI APOTEK ARJASA KOTA MALANG - Mayang Aditya Ayuning Siwi (Jurnal Kesehatan Hesti Wira Sakti, 2020)
Pharmaceutical service standards in pharmacies are the basis for services in pharmacies and as benchmarks that are used as guidelines for pharmaceutical personnel in carrying out pharmaceutical services. This study aims to determine the suitability of the implementation of pharmaceutical service standards in pharmacies based on Permenkes No.73 of 2016 at Arjasa Pharmacy in Malang. This research is a non-experimental research with descriptive research type. The population in this study were all pharmacists managing the Arjasa pharmacy and the sample in this study were 7 pharmacists who were willing to become respondents. The data was collected by using a questionnaire containing 39 statements. The questionnaire was filled in by the respondent, namely the pharmacist who manages the Arjasa Pharmacy in Malang. Based on the results of the research that has been done. This is based on instructions from the Director of Arjasa Pharmacy, the pharmacy that is used as a place of research is Arjasa pharmacy 1 and 2 and which are addressed in Karangploso and Blimbing. The results of research can be concluded that the suitability of the implementation of pharmaceutical services with Health Ministry Rules of Republic Indonesia Number 73 of 2016 obtained a percentage of 95.24% in the field of pharmaceutical preparation management, 100% for clinical pharmacy services.